The ecology of peatland bryophytes - adaptations and competition in alkaline fens - Vicherová, Eliška (Jihočeská univerzita, 2020)
This dissertation thesis studies adaptations and competition of peatland bryophytes in alkaline fens. Specifically, it examines the existence of plant-plant interactions through volatile organic compounds in peatland bryophytes and surveys impacts of water chemistry on composition of bryophyte communities and species survival. It also aims to resolve principles behind calcicole-calcifuge behaviour of peatland bryophytes and mechanisms behind calcium toxicity.
The ecology of peatland bryophytes - adaptations and competition in alkaline fens
Keywords: peatland bryophytes; ecology; calcitolerance; interactions; peatland bryophytes; ecology; calcitolerance; interactions